Client perspectives of therapist self-disclosure: Violating boundaries or removing barriers? - Audet, Cristelle T. (Counselling Psychology Quarterly, 2011)
There has been a longstanding ethical debate in the literature on therapist self-disclosure and its appropriateness in psychotherapy practice. Although multiple therapeutic benefits have been documented, risks commonly identified with therapists providing personal information to clients are that it can blur client-therapist boundaries and diminish important professional qualities associated with the therapist's role. Little is known about the impact therapist disclosure may have on therapy boundaries and professional qualities from the perspective of actual clients. This qualitative study provides a window into the experiences of nine participants of boundaries and therapist professionalism in the context of receiving non-immediate personal disclosures. Findings indicate therapist disclosure can, but does not necessarily, generate boundary issues, can either enhance or diminish perceived credibility and competence and can enhance or compromise the client's view of both therapist and client roles. Results are situated within the ethics debate. Further exploration of the relationship between therapist disclosure and the client role is recommended.